Demystifying mercury geochemistry in contaminated soil–groundwater systems with complementary mercury stable isotope, concentration, and speciation analyses. Issue 9 (4th January 2022) - McLagan, D. S.; Schwab, L.; Wiederhold, J. G.; Chen, L.; Pietrucha, J.; Kraemer, S. M.; Biester, H.
Abstract : A holistic multi-analyses (led by Hg stable isotope analysis), multi-media, multi-site approach to improving contaminated site Hg geochemistry, particularly process tracing. Abstract : Interpretation of mercury (Hg) geochemistry in environmental systems remains a challenge. This is largely associated with the inability to identify specific Hg transformation processes and species using established analytical methods in Hg geochemistry (total Hg and Hg speciation). In this study, we demonstrate the improved Hg geochemical interpretation, particularly related to process tracing, that can be achieved when Hg stable isotope analyses are complemented by a suite of more established methods and applied to both solid- (soil) and liquid-phases (groundwater) across two Hg 2+ -chloride (HgCl2 ) contaminated sites with distinct geological and physicochemical properties. This novel approach allowed us to identify processes such as Hg 2+ ( i.e., HgCl2 ) sorption to the solid-phase, Hg 2+ speciation changes associated with changes in groundwater level and redox conditions (particularly in the upper aquifer and capillary fringe), Hg 2+ reduction to Hg 0, and dark abiotic redox equilibration between Hg 0 and Hg(ii ). Hg stable isotope analyses play a critical role in our ability to distinguish, or trace, these in situ processes. While we caution against the non-critical use of Hg isotope data for source tracing in environmental systems, due to potentially variable source signatures and overprinting by transformation processes, our study demonstrates the benefits of combining multiple analytical approaches, including Hg isotope ratios as a process tracer, to obtain an improved picture of the enigmatic geochemical behavior and fate of Hg at contaminated legacy sites.